Duodenal acidification induces gastric relaxation and alters epithelial barrier function by a mast cell independent mechanism - Vanheel, Hanne (Sci Rep, 2020)
Duodenal hyperpermeability and low-grade inflammation in functional dyspepsia is potentially related to duodenal acid exposure. We aimed to evaluate in healthy volunteers the involvement of mast cell activation on the duodenogastric reflex and epithelial integrity during duodenal acidification. This study consisted of 2 parts: (1) Duodenal infusion of acid or saline during thirty minutes in a randomized, double-blind cross-over manner with measurement of intragastric pressure (IGP) using high resolution manometry and collection of duodenal biopsies to measure epithelial barrier function and the expression of cell-to-cell adhesion proteins. Mast cells and eosinophils were counted and activation and degranulation status were assessed. (2) Oral treatment with placebo or mast cell stabilizer disodiumcromoglycate (DSCG) prior to duodenal perfusion with acid, followed by the procedures described above. Compared with saline, acidification resulted in lower IGP (P < 0.01), increased duodenal permeability (P < 0.01) and lower protein expression of claudin-3 (P < 0.001). Protein expression of tryptase (P < 0.001) was increased after acid perfusion. Nevertheless, an ultrastructural examination did not reveal degranulation of mast cells. DSCG did not modify the drop in IGP and barrier dysfunction induced by acid. Duodenal acidification activates an inhibitory duodenogastric motor reflex and, impairs epithelial integrity in healthy volunteers. However, these acid mediated effects occur independently from mast cell activation.